APPLICATION OF LEARNING BY DOING METHOD AS THE IMPLEMENTATION OF PRAGMATISM PHILOSOPHY IN DEVELOPING STUDENTS' UNDERSTANDING ON NARRATIVE TEXT THROUGH ONLINE CLASS IN THE PANDEMIC TIME - Ghea Putri Melati (International Journal of Teaching and Learning, 2024)
The COVID-19 pandemic has forced the world of education to change its system and use a new paradigm to deal with emerging problems. All levels of society must prepare themselves to do online activities by utilizing technology in order to learn from home. The learning using online media which provides opportunities for students to develop themselves independently, guided by teachers in distance learning through online classes. Many new problems arise, not only faced by students but also by parents and teachers. This is because they are not familiar with distance learning. The problem faced by teachers is that it is difficult to control students let alone make them study seriously and effectively. English as a foreign language is a big problem for students and parents to carry out learning without direct teacher assistance. Moreover, narrative text is a difficult material for students of SMPN 2 Tasikmalaya to master. The researcher found that the learning by doing method initiated by John Dewey would help students to better understand narrative texts. The learning by doing learning method is a learning method based on the philosophy of pragmatism. Researchers tried to apply this method to grade 9A students of SMPN 2 Tasikmalaya in the 2021-2022 school years. After applying the method initiated by John Dewey, there was a significant improvement in the ability to understand narrative texts. This can be seen from the value they get. The increase in value reached 31.4%.